DWB-AES: an implementation of dynamic white-box based on AES - Bin WANG; Si CHEN; Jiadong CHEN; Xing WANG (Tongxin xuebao)
The resources of IoT devices are limited.Therefore, security, flexibility and lightweight cryptographic modules are required.The idea of white-box cryptography can meet the needs of IoT devices.In common AES white-box implementations, keys are bound to look up tables.So the look up tables must be changed when the keys are changed.It is not flexible enough in practical applications.To solve this problem, a dynamic white-box implementation method for AES, which was called DWB-AES, was proposed.By changing the boundary between rounds, all operations of the encryption and decryption process were performed by looking up the tables, and the tables and the keys were respectively confused, so that the entire encryption and decryption process did not expose the key information.The look up tables need not to be changed every time when the keys changed, which was more practical.The security analysis of DWB-AES shows that the DWB-AES has higher white-box diversity and ambiguous, it can resist BGE attack and Mulder attack.